Distance to the Galactic Center 7′ Halo from H I Absorption - Debangan Maji; Subhashis Roy (The Astrophysical Journal, 2025)
Using archival data, we have made an H I absorption study of the 7 ${}^{{′} }$ halo surrounding the Sgr A complex, observed toward the Galactic center (GC) region. We find strong H I absorption near velocities of −53 km s ^−1 , which is due to the 3 kpc arm, placing it beyond 5 kpc from us. We further examined the H I absorption properties toward five different parts of the 7 ${}^{{′} }$ halo. Absorption by the +50 km s ^−1 GC cloud is seen toward only three parts of the halo, but not toward the other two regions. Strong emissions in CO and CS are, however, identified toward all the above five parts of the halo by the +50 km s ^−1 GC molecular cloud. This does show that the 7 ${}^{{′} }$ halo is partly behind and partly in front of the 50 km s ^−1 cloud. To our knowledge, this for the first time clearly shows the 7 ${}^{{′} }$ halo to be located at the same distance as the +50 km s ^−1 molecular cloud, i.e., at the GC region.